KETAHANAN HORTIKULTURA DENGAN PEMANFAATAN LUMPUR TINJA DI RT 07 KELURAHAN SAWAH LEBAR BARU KOTA BENGKULU - Eko Sumartono; Basuki Sigit Priyono; Sriyoto Sriyoto (Universitas Bengkulu, 2016)
Nowadays many limitations in the society of Sawah Lebar Baru inspire further development to use their yards and sludge around them in area. This development program can be used to fulfill the horticulture needs of people in that area which is done by planting vegetables in their own yards in order to increase family income. The output of this development program is to increase housewives’ knowledge and skills about the use of sludge as growing medium in the polybags. The socialization and training methods are used in this program. Socialization is done by using personal approach and group approach methods. Training is done to inform about preparation, growing medium filling, and planting vegetables in the polybags. As the effort to maximize the use of yards and increase family income, it is still needed to develop knowledge and skills about the use of sludge as the vegetables growing medium. The role of change agent and communiy services still needed to be increased.Keywords: development, community services, backyard. sludge